Iatrogenic Great Cardiac Vein Anastomosis during Coronary Artery Bypass Surgery - Bagherli, Alireza; Bews, Hilary; Vo, Minh; Ducas, John; Jassal, Davinder S.; Ravandi, Amir (International Journal of Angiology, 2017)
Inadvertent anastomosis of the left internal mammary artery (LIMA) or a saphenous vein graft (SVG) to the great cardiac vein (GCV) is a rare complication of coronary artery bypass grafting (CABG). We present two cases with a LIMA to GCV and a SVG to GCV anastomosis, respectively, resulting in angina and dyspnea in the postoperative state. As an alternative to repeat CABG, both patients underwent percutaneous coronary intervention with percutaneous coil embolization or implantation of an Amplatzer vascular plug within the bypass graft to GCV conduit. This report highlights that percutaneous options exist for the relief of ischemic symptoms in this rare clinical setting.
Keywords: angioplasty; cardiac catheterization; cardiac surgery; coil embolization; coronary intervention; ischemia; non-ST elevation myocardial infarction